The Benefits of the University of Health and Allied Sciences to its Host Communities - Amoah, Richard; Anomah, Felix Kwaku (Ghana Journal of Higher Education Management, 2023)
In the last four decades, universities have been under increasing pressure to prove their relevance towards the development of their host communities. This study, from this background generally builds on existing research by assessing the benefits of UHAS to its host community. The study specifically examined the benefits of the university on indigenes and other community members and further assessed the factors that determine the impact of the university on its host community. The study adopted the qualitative research paradigm. In all, the study utilized a sample of 20 respondents comprising 5 university staff, 10 indigenes, and 5 people from operating businesses close to the university. Respondents were selected using a purposive sampling strategy. Interviews were used as the instrument of data collection. Results of the study reveal that the university’s host communities have benefited from the establishment and operation of the university in the form of increased access to education, employment creation, boosting of the local economy, and access to other community services. The study culminates by proffering policy implications. Among other measures, it is recommended that the University creates a strategic community engagement plan, create incentive structures that promote faculty community engagement, and aligns its programs with local economy needs.